Unmodified mRNA in LNPs constitutes a competitive technology for prophylactic vaccines. (December 2017) - Lutz, Johannes; Lazzaro, Sandra; Habbeddine, Mohamed; Schmidt, Kim; Baumhof, Patrick; Mui, Barbara; Tam, Ying; Madden, Thomas; Hope, Michael; Heidenreich, Regina; Fotin-Mleczek, Mariola
Abstract mRNA represents a promising new vaccine technology platform with high flexibility in regard to development and production. Here, we demonstrate that vaccines based on sequence optimized, chemically unmodified mRNA formulated in optimized lipid nanoparticles (LNPs) are highly immunogenic and well tolerated in non-human primates (NHPs). Single intramuscular vaccination of NHPs with LNP-formulated mRNAs encoding rabies or influenza antigens induced protective antibody titers, which could be boosted and remained stable during an observation period of up to 1 year. First mechanistic insights into the mode of action of the LNP-formulated mRNA vaccines demonstrated a strong activation of the innate immune response at the injection site and in the draining lymph nodes (dLNs). Activation of the innate immune system was reflected by a transient induction of pro-inflammatory cytokines and chemokines and activation of the majority of immune cells in the dLNs. Notably, our data demonstrate that mRNA vaccines can compete with licensed vaccines based on inactivated virus or are even superior in respect of functional antibody and T cell responses. Importantly, we show that the developed LNP-formulated mRNA vaccines can be used as a vaccination platform allowing multiple, sequential vaccinations against different pathogens. These results provide strong evidence that the mRNA technology is a valid approach for the development of effective prophylactic vaccines to prevent infectious diseases. Vaccine technology: Repurposing the genetic messenger Vaccines based on mRNA provoke strong immune responses after a single dose. mRNA is commonly known as the 'genetic messenger' cousin of DNA and a crucial mediator of protein production. Now, research led by Mariola Fotin-Mleczek, of Germany's CureVac AG, demonstrates that mRNA can be developed to produce virus fragments, called antigens, that can prime a vaccinee's immune system against a pathogen. Testing their vaccine platform, the team created mRNA coding for rabies and influenza antigens, and used intramuscular injection to inoculate non-human primates. A single dose elicited strong immune responses, which the team then successfully maintained through booster vaccinations for an observation period of 1 year. The responses outperformed those of licensed vaccines against rabies and influenza type H3N2. This research shows that mRNA has promise as a versatile, cost-effective, rapidly scalable vaccine technology.